(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
Conditions at SD N 02 Bringin show low critical thinking skills which have an impact on low student learning outcomes in grade 5 mathematics learning. This is due to the lack of teacher variation in using appropriate learning models so that learning is less attractive to students’ curiosity. Based on these conditions, researchers conducted research that aimed to describe the syntax of the 3 CM learning model Learning and with this model it can improve critical thinking skills and mathematics learning outcomes of 5th grade students of SD N Bringin 02. The results showed that critical thinking skills in action I got an average of 76% with the critical category, in action II the average critical thinking skills increased to 88% with very critical category. For learning outcomes in action I as many as 11 students with a percentage of 46% have received a complete score, and as many as 13 students with a percentage of 54% have not completed. In action II there was an increase, 21 students with a percentage of 87% were declared complete and the remaining 3 students with a percentage of 13% were declared incomplete. Based on the results of research conducted at SD Negeri Bringin 02 for grade 5 by applying the 3 CM model Learning assisted by concrete media, especially in mathematics, is proven to be able to improve critical thinking skills and student learning outcomes